1989
DOI: 10.1016/s0006-3495(89)82683-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface pH controls purple-to-blue transition of bacteriorhodopsin. A theoretical model of purple membrane surface

Abstract: We have developed a surface model of purple membrane and applied it in an analysis of the purple-to-blue color change of bacteriorhodopsin which is induced by acidification or deionization. The model is based on dissociation and double layer theory and the known membrane structure. We calculated surface pH, ion concentrations, charge density, and potential as a function of bulk pH and concentration of mono- and divalent cations. At low salt concentrations, the surface pH is significantly lower than the bulk pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
93
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 46 publications
11
93
0
Order By: Relevance
“…is the Scatchard plot [23] which should give a straight line with a slope of -K and an intercept that gives n. For any added concentration of Eu a+ to a sample of dlbR, if the concentration of the free Eu ~+ (L) is determined, the moles of Eu a÷ hound v can be calculated. We have used chelating agents to enhance the fluorescence [28] of the free Eu a+ to determine its concentration after separating it from the bR and its bound Eu ~÷.…”
Section: The Methodsmentioning
confidence: 99%
“…is the Scatchard plot [23] which should give a straight line with a slope of -K and an intercept that gives n. For any added concentration of Eu a+ to a sample of dlbR, if the concentration of the free Eu ~+ (L) is determined, the moles of Eu a÷ hound v can be calculated. We have used chelating agents to enhance the fluorescence [28] of the free Eu a+ to determine its concentration after separating it from the bR and its bound Eu ~÷.…”
Section: The Methodsmentioning
confidence: 99%
“…It has been shown that this transition reflects the protonation state of the primary proton acceptor Asp-85 (22,31). The purple to blue transition is directly affected by the proton concentration at the protein surface, which depends on the surface charge (30,32). Therefore, the apparent pK a of this transition is strongly dependent on ionic strength.…”
Section: Characterization Of the Unphotolyzed Single And Double Mutanmentioning
confidence: 99%
“…Jang and El-Sayed also found an increased emission and degree of hydration of Eu3+ with the delipidated membrane vs the native membrane. They suggested that these differences were probably due to changes in binding site conformation and not to new sites forming upon delipidation, and were therefore protein-specific, but Szundi and Stoeckenius (1989) proposed that the Eu3+ could have been bound to phospholipids in the purple membrane and to protein carboxyls in the delipidated membrane. Jang and El-Sayed also suggested that a conformational change in the bR active site occurs (the conformation becomes more open) in the delipidated membrane such that cations are no longer required for the deprotonation of the Schiff base, as in Corcoran et al (1987) for the native membrane; the active site is more heterogeneous.…”
Section: Lipid Effectsmentioning
confidence: 99%